Bagas Godang as an Inheritance for the Youngest Children (Namenekna) in the Traditional Inheritance of Mandailing Natal Perspective ‘Urf - Ahmad Safri; Sugeng Wanto (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2024)
Bagas godang is an heirloom house or a house left by parents that are passed down to the youngest child. It is a traditional custom in Purba Baru Village, Lembah Sorik Marapi District. This research aims to find out or analyse how the practice of distributing inheritance to the youngest child (namenekna) as the heir who gets bagas godang in the traditional Mandailing Natal inheritance in Purba Baru Village, Lembah Sorik Marapi District is appropriate and achieves the portion of justice with the existing provisions in 'urf. This research was conducted using empirical research, also known as field research, using field data as the primary data source, such as the results of interviews and observations. Judging from the number of problems resolved with the help of Hatobangon, he is a traditional figure whose majority of decisions are accepted by the community, outside his realm of severe cases, namely murder, drugs and others. This is why the Hatobangon decision, according to some religious figures, is included in 'urf shahih if there is justice and benefit, whereas if there is no justice and there are those who are harmed then it will be 'urf fasid. This is a customary custom in which the heirs conduct deliberations first so that the heirs feel fair and are not disadvantaged. On the other hand, if problems occur in this tradition, certain situations can still be changed through further deliberation.